2016
DOI: 10.1016/j.jegh.2015.12.001
|View full text |Cite
|
Sign up to set email alerts
|

A cohort study of chronic diseases for Mongolian people: Outline with baseline data of the Moncohort study

Abstract: Many Mongolian people suffer from non-communicable chronic diseases. In order to plan preventive strategies against such diseases, we designed a community-based prospective cohort study of chronic diseases, called the Moncohort study, in Mongolia. This is the first nationwide large-scale cohort study of chronic diseases. This paper describes the study's rationale, design and methods with baseline data. Mongolian residents aged ⩾40years were selected nationwide from many geographic regions in 2009. Data were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…While contingent on efforts to increase the diversity and quality of foods supplied, one important strategy that will improve both micronutrient intake and NCD risk in Mongolia will be the revision of the country's dietary guidelines, which are both inadequately publicized and are not well-informed by nutrition science [53]. Finally, research priorities going forward should include the compilation, dissemination, and periodic update of national food composition data as many unique local dairy products and other foods cannot be easily imputed using foreign data; development, validation, and dissemination of standardized dietary assessment instruments; implementation of a national dietary surveillance system (potentially co-opting available household and commercial data platforms [54]); and continued development and follow-up of cohorts and other study populations for the purpose of nutritional epidemiology [55].…”
Section: Discussionmentioning
confidence: 99%
“…While contingent on efforts to increase the diversity and quality of foods supplied, one important strategy that will improve both micronutrient intake and NCD risk in Mongolia will be the revision of the country's dietary guidelines, which are both inadequately publicized and are not well-informed by nutrition science [53]. Finally, research priorities going forward should include the compilation, dissemination, and periodic update of national food composition data as many unique local dairy products and other foods cannot be easily imputed using foreign data; development, validation, and dissemination of standardized dietary assessment instruments; implementation of a national dietary surveillance system (potentially co-opting available household and commercial data platforms [54]); and continued development and follow-up of cohorts and other study populations for the purpose of nutritional epidemiology [55].…”
Section: Discussionmentioning
confidence: 99%
“…The health burden of non-communicable diseases such as cardiovascular illness and diabetes mellitus has increased year by year in Mongolia and is thus becoming a leading cause of kidney disease. Large cross-sectional studies conducted in six regions of the world revealed that hypertension, diabetes, obesity, and high cholesterol level were all independently associated with chronic kidney disease, and the prevalence of chronic kidney disease was 18.0% (15.5-20.8%) in Mongolia [8][9][10][11][12] .…”
Section: Introductionmentioning
confidence: 99%
“…Although there are some research studies on the prevalence of renal diseases and its risk factors in Mongolia, we are aware of only one single study on the use of potentially inappropriate drugs in the elderly [7][8][9][10][11][12] . We are unable to identify other peerreviewed studies on the use of potentially inappropriate drugs in elderly Mongolian patients with kidney disease.…”
Section: Introductionmentioning
confidence: 99%